Does Prosodic Bootstrapping Play Any Role in the Acquisition of Auxiliary Fronting in English?. (23rd February 2013) - Guimarães, Maximiliano
<x xml:space="preserve">Abstract</x> Abstract. In his broad criticism of the biolinguistic approach to the theory of grammar, Everett (2005, 2006) discusses, among other things, the classical instance of the Poverty of the Stimulus Argument drawn from auxiliary fronting in English, originally made by Chomsky. Everett claims that: (i) the rule responsible for the attested pattern would not be structure‐dependent, as it could be defined without making reference to hierarchical notions like "matrix clause" or "subordinate clause"; (ii) such rule requires no domain‐specific innate bias in order to be learned, given that the stimulus in the primary linguistic data would be "rich" enough for the child to figure out the relevant grammatical mechanism at work; and (iii) such "richness" would lie in prosodic information present in the data, which, according to him, has been largely neglected by generativists. The aim of this article is to show that all three parts of Everett's alternative analysis are conceptually problematic and empirically unsupported. As a matter of logic, the very idea that children rely on prosodic cues to learn the lexicon and the syntax presupposes UG. Moreover, I offer new experimental evidence that a significant portion of the facts is incompatible with Everett's account. Therefore, his attempt to refute linguistic nativism misses the target.